​​A Robot Locomotion Mechanism Powered by Wind Energy - WANDER-Bot​ - ​​Kurian​, ​​Sam Valavuchirakal​ (Cranfield University, 2025)
This report discusses the experimental development of WANDER-Bot: an early mechanical locomotion solution design concept for planetary exploration. It requires low-cost, low-power, low-storage, and is designed to be easily manufactured and assembled onsite using ISRU manufacturing methods. It is a design proposal which aims to address the existing limitations of space robotic missions and locomotion solutions: their high-cost, power budget constraints caused by degrading solar and RTG power sources, large storage requirement for transportation on the launch vehicle, high complexity, and difficulty to maintain and repair. Titan has been proposed as the future planetary environment exploration application for the system. The WANDER-Bot integrated system is composed of 3 main mechanisms: a Savonius turbine wind energy capture mechanism, reduction gearing mechanism to multiply torque, and a Jansen legged walking mechanism for locomotion. The robot uses simple mechanical linkages and assembly methods to lower cost and improve maintainability. Its 3D printable design allows future ISRU manufacturing potential, and its wind-powered driving mechanism offsets the electrical power demand for locomotion. Developed with consideration of planetary environments such as Titan, WANDER-Bot demonstrates the ability to walk forward in omnidirectional wind conditions, on rough, firm terrain at relatively low windspeeds, with a Titan-equivalent weight offset. This report covers the design evolution of the integrated robot system, through prototype iterations, of its individual constituent mechanisms. It documents the challenges faced, design improvements, and performance analysis through the experimental testing campaign. Experiments include walking gait analysis to ensure locomotion smoothness and stability, verifying motion simulations, turbine RPM performance at different windspeeds, and the self-start threshold windspeed for each integrated system iteration. It documents how these experimental findings informed design changes in future iterations. Successes and limitations of the design and testing is identified, along with future improvements to increase performance and environmental representation. The report concludes that this early WANDER-Bot prototype is not yet applicable for the environment in its current state, but the system demonstrates the feasibility of the low-cost, wind-powered, additively manufactured, easily maintainable locomotion solution. Future work is proposed to take this design further to develop maturity for the proposed application, such as steering mechanisms, variable speed control, and basic robot perception and autonomy for obstacle avoidance.
Keywords: ​​Jansen mechanism; Titan planetary exploration; Savonius wind turbine; low-cost; ISRU; Experimental testing and development